Europe's Birds An Identification Guide - Swash, Andy (WILDGuides, 2022)
The most comprehensive single-volume photographic guide to Europe's birds ever produced-from the authors of the acclaimed Britain's BirdsCovering more than 900 species, and illustrated with over 3,800 photographs, this is the most comprehensive, authoritative and ambitious single-volume photographic guide to Europe's birds ever produced. Detailed descriptions provide the information necessary to identify the birds of Europe in all their plumages-male, female, breeding, non-breeding, adult and immatures, as well as distinctive subspecies-yet the book is easy-to-use, practical and accessible. Birdwatchers of any ability will benefit from the clear text, details on range, status and habitat, and an unrivalled selection of photographs. Chosen to be as naturalistic and informative as possible, the images are also stunning to look at, making this a beautiful book to enjoy, as well as an up-to-date and essential source of identification knowledge.Europe's Birds is produced by the same team that created Britain's Birds, which has been described as "without doubt the best photo guide on the market" (Andy Stoddart, Rare Bird Alert). The authors include top-class wildlife photographers, writers and editors, and an imaginative, highly skilled designer. All are experienced birdwatchers themselves, who know what is needed and what is useful in an identification guide for birdwatchers living or travelling in Europe.Covers all 914 species ever recorded in Europe, including established introductionsDescribes all distinctive plumages and subspeciesProvides details of vocalizations, flight action and favoured habitatsFeatures more than 3,800 photographs, including comparison pages of birds in flightIncludes 540 maps, prepared in association with BirdLife InternationalEnables direct comparison of similar species